HUBUNGAN KEKUATAN OTOT LENGAN BAHU DENGAN KEMAMPUAN SERVICE BAWAH PERMAINAN BOLA VOLI SISWA PUTRA KELAS V SDN 21 TELUK LATAK KECAMATAN BENGKALIS - Firdaus, Predi; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, type of research is correlational. Correlation is a statistical tool, which can be used to compare the results of measurements of two different variables in order to determine the degree of association between variables. Populations in this research is male students of SDN 21 Teluk Latak Kecamtan Bengkalis totaling 14 students. Selection of samples using total sampling technique. From the calculation of correlation values can be seen that the large value of relationship strength arm and shoulder muscles with under service capabilities men's volleyball fifth grade students of SDN 21 Teluk Latak Kecamtan Bengkalis is 0.594 with rtabel value = 0.532, it means rhitung = 0.594> rtabel = 0.532 and it can be said that there is a relationship of muscle strength in the arms and shoulders under service capabilities men's volleyball games grade students of SDN 21 Teluk Latak Kecamtan Bengkalis. From the results of the calculation are known t = 2.56, while ttabel with df = n-2 = 14-2 = 12 at 95% confidence level is 1.782. Ho hypothesis testing criteria accepted if thitung smaller than ttabel while the calculation results show that t = 2.56> t table = 1.782, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that